Elephant management in Nyaminyami District, Zimbabwe: turning a liability into an asset - Russell Taylor (Pachyderm)
In Nyaminyami District on the southern shores of Lake Kariba, 20,000 people share Omay Communal Land with some 2,000 elephants and a range of other large wild animals. Elephants are a major cause of conflict between wildlife and people due to the damage inflicted upon crops and property plus injury or death to human life. The CAMPFIRE programme is being directed towards reducing conflict between elephants and human beings and increasing tolerance towards these animals. The merits of these approaches are outlined and the implications for the long term conservation of elephants discussed.